Educational challenges in videos (Vlog) on YouTube and the ways to face them - Field study on primary school teachers in Jeddah, Kingdom of Saudi Arabia - - Barakat, Fahad Mohammed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to explain the conceptual framework of educational challenges in the YouTube program "vlog", in addition to identifying ways to meet those challenges from the teachers' point of view. This study relied on the descriptive approach, and questionnaires were conducted as a tool to collect data and information, the study sample consisted of (705) teachers from Jeddah. The results showed that the most prominent educational challenges in (vlog) videos on YouTube were that the study sample members agreed on educational challenges in (vlog) YouTube videos with an average arithmetic score of (3.49 of 5) and that the study sample members agreed with the educational challenges in (vlog) videos on YouTube regarding the negative aspects of the (vlog) program, with an average score of (3.38 out of 5) And that the study sample members agree on the means of facing educational challenges in (vlog) videos on YouTube with an average of (3.80 out of 5.00).
Keywords: Educational challenges; YouTube; Vlogs; Primary school teachers; Kingdom of Saudi Arabia